2012
DOI: 10.1364/ol.38.000016
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stokes wing of femtosecond laser filament supercontinuum in fused silica

Abstract: We have demonstrated that in the IR pulse filament the anomalous dispersion of fused silica leads to the formation of an isolated anti-Stokes wing (ASW), which is located in the visible region of the supercontinuum (SC). It is shown that the isolated ASW is formed by the interference of the light field of a SC undergoing anomalous group velocity dispersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Saliminia et al [10] and Faccio et al [11] have shown the emergence of a broad peak in the visible part of the supercontinuum spectra generated by a 1.5-μm filament. Recent reports on supercontinuum emission from filaments at longer wavelengths confirm this observation while showing that filamentation in the anomalous dispersion regime gives rise to a broader continuum of over 3.3 octaves that could ideally self-compress to a single-cycle pulse [13][14][15][16].…”
mentioning
confidence: 70%
“…Saliminia et al [10] and Faccio et al [11] have shown the emergence of a broad peak in the visible part of the supercontinuum spectra generated by a 1.5-μm filament. Recent reports on supercontinuum emission from filaments at longer wavelengths confirm this observation while showing that filamentation in the anomalous dispersion regime gives rise to a broader continuum of over 3.3 octaves that could ideally self-compress to a single-cycle pulse [13][14][15][16].…”
mentioning
confidence: 70%
“…[17] demonstrate unexpected long light-bullet propagation and reveal also another interesting point. The propagation dynamics are accompanied by the generation of blueshifted radiation [28], a phenomenon which is observed also under different conditions [8,[29][30][31][32] even for short filament lengths.…”
mentioning
confidence: 86%
“…The angle-integrated as well as the axial SC spectra show an intense blue-shifted peak located in the visible range, which is identified as an axial component of the conical emission and whose blue-shift increases with increasing the wavelength of the driving pulse [157,158]. Various aspects of the spectral broadening and SC generation, such as energy content, stability of the carrier envelope phase, etc., were studied in connection with formation and propagation dynamics of spatiotemporal light bullets [77, 159, 3 μm laser pulse in a 3 mm-long fused silica sample versus the input pulse energy.…”
Section: ]mentioning
confidence: 99%